Irrigation in nopal influences the storage and packaging of tuna - Varela-Gámez, Yamileth; Caldera-Arellano, Ana Karen; Zegbe, Jorge A.; Serna-Pérez, Alfonso; Mena-Covarrubias, Jaime (Revista Mexicana de Ciencias Agrícolas, 2018)
Irrigation in the quality and shelf-life of tuna has not been documented so far. The objective of this research was to study the influence of irrigation on quality, shelf-life and packaging of tuna ‘Cristalina’ and ‘Amarilla Olorosa’ after a cooling period. The fruits were harvested from the following irrigation treatments: no irrigation (NI) as control, supplementary irrigation (SI) and full irrigation (FI). Three batches of 72 fruit (24 fruits per treatment), each made to evaluate its quality at harvest and after storage at room temperature (SRT) and cooling over seven days in room conditioning (R+RT). At harvest, the fruit weight (FW) of ‘Cristalina’waslowerinNIplantsthanSIorFI.Thefirmness (F), the concentration of total soluble solids (CSS) and fruit dry matter (DM) were similar between the treatments. After SRT or R+RT, the FI held high the FW and F, but reduced the DM. In both storage systems, loss of fruit weight was lower in the FI or SI. The tuna ‘Amarilla Olorosa’ behaved like ‘Cristalina’ and had no damage by fungi or cold. Compared to the FI, SI induced similar responses in both types of tuna and saved ≈56% of irrigation water; therefore, this irrigation strategy could be suggested for this and similar agro-ecological areas.
Keywords: Opuntia spp.; fruit quality; post-harvest of tuna